Solar Panel and Wireless Power Transmission System as a Smart Grid for Electric Vehicles - Bendib, M. E.; Mekias, A. (Engineering, Technology & Applied Science Research, 2020)
In this work, a smart grid system consisting of solar panels and a battery is presented for an electric or hybrid vehicle. For the integration of green power in our system, solar panels are used to charge the accumulator while the power exchange between the vehicle and the grid is realized by power wireless transfer. This paper presents the design, control, and tests of the wireless power transmission, using the basics of magnetic resonant coupling. Numerical data of the power transfer efficiency of the receiver are presented. Graphs are given to show the comparison of power and efficiency with the distance of the coils. Magnetic and electric models of the system are used to analyze the problem. Using the analysis outcome, a compromise is made to come to an acceptable design achieving both requirements. In particular, appropriate design parameters and resonance frequency are obtained. The analytical results are confirmed by 3D Finite Element Method (FEM) analysis.